Land inventory: accounting practical aspect - T.P. Ostapchuk; D.V. Gavrylovska (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The article studies the methodical approaches to land inventory as absolute ownership and received for use from other persons. The normative regulation of land inventory for land management purposes and its influence on the main stages of inventory of land for accounting purposes is investigated. The ways of improvement of documentation of operations connected with land inventory are considered. Influence of features of lands of different categories on the process of their inventory is established.